Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content1. Practice of Islamic Education Teachers of Prophetic Methods in Arousing Motivation When Teaching the Holy Quran in the Primary Stage in Jeddah GovernorateMr. Abdulaziz Abdullah Alsahli2. Evaluating the content of the English book for the third grade secondary in Saudi Arabia in light of the future skillsMrs. Lama Abdullah AL-Tamimi, Dr. Eman Hussain Abu Saleem3. Analyzing the Content of English Language Textbook for the Sixth Elementary Grade  in the Kingdom of Saudi Arabia in Light of Multiple Intelligences TheoryMrs. Amani Abdullah Hamad Alfaisal , Prof. Maha Ibrahim Al-Kaltham4. Digital Citizenship Dimensions in Arabic Language Curricula for Secondary Stage from View of Its Teachers in Makkah Al Mukarramah: Qualitative and Quantitative StudyMrs. Afnan Omar Masoud , Prof. Hanan Sarhan Al-Nimri5. The impact of using Virtual laboratory applications inside the classroom on development academic achievement in science among eighth grade studentsMr. Omar Hamdan Salim Alhosni6. The Effectiveness of Using Some Active Learning strategies on the development of grammatical skills of eighth grade female students in the Republic of YemenMrs. Haifa Ali Al-Wajih7. Content Analysis of Digital Skills Course for Primary Stage in the Kingdom of Saudi Arabia in Light of Digital Citizenship ValuesMrs. Nouf Majed Saad Alshuhaywin,  Prof. Ajlan Mohammed H. Alshehri
Keywords: Journal of Curriculum and Teaching Methodology